Marvel : meet the super heroes. - Ilnitzki, Megan; Vitale, Brooke (World of reading. Level Pre-1, 2017)
"Get to know the characters from Guardians of the Galaxy, Iron Man, Spider-Man, and more in this boxed set featuring twelve 10-page Pre-Level 1 readers."--Amazon.com.